Manajemen Persediaan Pada UMKM Martabak Telor Mini - Agustian, Muhamad Alif; Romadon, Barkah Ibnu; Purnama, Muhamad Elki; Mushoffa, Ahmad Syifaq (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Mini Egg Martabak is a business plan about egg martabak which is given a touch of cheese, sausage and casserole. Mini egg martabak is a traditional food made from spring roll skin which is topped with toppings and fried until crispy. This mini egg martabak has a savory taste because there is additional cheese in it and has a spicy taste if cayenne pepper or chili powder is added to it. This mini Egg Martabak is a home business that is sold at affordable prices with guaranteed quality raw materials. The inventory management for these mini egg martabaks is the main raw materials which include eggs, spring roll skins, spring onions, cabbage, seasonings, cooking oil and toppings. The purpose of this research is to determine the amount of inventory, the amount of material needed and determine a method for preparing production materials. Determine the ordering costs for each raw material using the Economic Order Quantity (EOQ) calculation.